2020
DOI: 10.1002/ejoc.202000299
|View full text |Cite
|
Sign up to set email alerts
|

Furfuryl Cation Induced Three‐Component Reaction to Synthesize Triazole‐Substituted Thioesters

Abstract: A furfuryl cation induced three‐component thioesterification reaction between thiols, 5‐bromo‐2‐furylcarbinols and azides is reported. This metal‐free method relies on the acetyl chloride/HFIP‐mediated cascade formal [3+2] cycloaddition/ring‐opening/thioesterification, which allows the efficient construction of a series of complex triazole‐thioesters linked with an (Z)‐olefin. Selenols are also suitable for this strategy. Further derivatization of thioesters highlighted the potential utility of our method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 131 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…A furufuryl cation-induced cascade reaction directly transforms furans to complex triazole-thioesters bearing a ( Z )-olefin (Scheme ). Strong Lewis acids such as SnCl 4 and TiCl 4 yielded complex reaction mixtures with only trace amounts of the desired thioester product, whereas weaker Lewis acids, such as ZnCl 2 , Dy­(OTf) 3 and Sc­(OTf) 3 , did not provide any of the desired product. AcCl and HFIP were used in DCM for the in situ generation of HCl, which provided high yields of the desired thioester.…”
Section: Pericyclic Reactionsmentioning
confidence: 99%
“…A furufuryl cation-induced cascade reaction directly transforms furans to complex triazole-thioesters bearing a ( Z )-olefin (Scheme ). Strong Lewis acids such as SnCl 4 and TiCl 4 yielded complex reaction mixtures with only trace amounts of the desired thioester product, whereas weaker Lewis acids, such as ZnCl 2 , Dy­(OTf) 3 and Sc­(OTf) 3 , did not provide any of the desired product. AcCl and HFIP were used in DCM for the in situ generation of HCl, which provided high yields of the desired thioester.…”
Section: Pericyclic Reactionsmentioning
confidence: 99%
“…Recently, Li and Xiao reported that a manganese complex bearing the electron-rich bipyridine ligand is an efficient catalyst in the selective oxidation of organosilanes into silanols by aqueous H 2 O 2 under neutral conditions . Inspired by this work and also as part of our ongoing interest in developing furan-based conversions, we hypothesized that Li’s manganese complex could be used in the catalytic oxidation of furan with low aromaticity, which delivers the oxygen-transfer from H 2 O 2 to the π-bond of the furan ring to lead to ring-opening and further Achmatowicz rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…R f = 0.3 (petroleum ether). 1 H NMR (400 MHz, CDCl 3 ): δ 6.19 (d,J = 3.1 Hz 1H),5.92 (d,J = 2.3 Hz 1H),4.85 (d,J = 17.5 Hz 2H),1H),2H), 2.29 (s, 3H), 1.74 (s, 3H). 13 C { 1 H} NMR (100 MHz, CDCl 3 ): δ 152.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…R f = 0.2 (1:1 petroleum ether/ethyl acetate). 1 H NMR (600 MHz, CD 3 OD_SPE): δ 7.51 (d, J = 16.2 Hz, 1H), 6.81 (d,J = 16.2 Hz,1H),1H),2H), 2.35 (s, 3H), 2.33−2.27 (m, 2H), 2.19−2.09 (m, 1H), 2.00− 1.93 (m, 1H). 13 C { 1 H} NMR (150 MHz, CD 3 OD_SPE): δ 199.…”
Section: Z)-1-(5-butyl-1-(1-(5-pentylfuran-2-yl)pentyl)-1h-123-triazo...mentioning
confidence: 99%
See 1 more Smart Citation